Mobile multi-user ATM platforms architectures, design issues, and challenges. - Kumar, P. (IEEE Network : the magazine of global information exchange)
Rapid growth in use of the Internet at and away from the workplace has spurred tremendous interest in the provision of anytime-anywhere network connectivity to mobile users. Commonly studied mobility scenarios involve users equipped with portable data terminals roaming around at slow to moderate speeds within a coverage area. Mobile IP and wireless ATM are examples of protocols designed for providing network connectivity to such mobiles in IP and ATM networks. A different application involving mobile multi-user platforms (MMUP) equipped with onboard private ATM networks is discussed in this article. Examples of such mobile platforms include airplanes, trains, and ships. The presence of an onboard network, multiple users, and potentially high speed of travel presents unique challenges in provision of internetwork connectivity to these MMUPs. Specific characteristics of MMUPs, architectural issues in design of the underlying cellular network, subnetwork mobility within ATM internetworks, location management of MMUPs, and multi-user connection handoffs on MMUP moves are the main issues addressed in the article. Network architectures and protocols developed for terminal mobility scenarios are evaluated for applicability in the present context, and new solutions are presented for problems unique to the MMUP application scenario